PENGARUH PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) DAN PERSEPSI MAHASISWA TENTANG PROFESI GURU TERHADAP MINAT MENJADI GURU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNIVERSITAS RIAU - Arini Zannah BR. Sinaga; Rr. Sri Kartikowati; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to describe the effect of Introduction to Schooling Environment (PLP) and student perceptions of the teaching profession on their interest in becoming a teacher at the. The population are all students of the 2016 Economic Education Study Program FKIP University of Riau, totaling 63 students. The sampling technique used was saturated sampling technique. The data collection method is to use a questionnaire. This questionnaire was used to obtain research data on the Introduction to Schooling Environment (PLP), student perceptions of the teaching profession, and interest in becoming a teacher. The questionnaire was distributed using media google form and the data collected were tabulated and analyzed using multiple linear regression with the help of SPSS version 22. The results showed that the Introduction to Schooling Environment (PLP) and student perceptions of the teaching profession simultaneously had a significant effect on the interest in becoming a teacher in program students Economic Education Study of FKIP, Riau University with the regression equation Y = 1.180 + 0.247X1 + 0.381X2 and contributed 50.4% to the interest in becoming a teacher, rest is influenced by other factors, namely motivation, needs, talents, mastery of science, family environment, social environment, and information on the world of work. This research is still not perfect, so it is hoped that the next researchers can conduct more thorough research on other factors that affect the interest in becoming a teacher and can increase or expand the population and research sample.Key Words : Introduction to Schooling Environment, Perception on Teacher Profession, Interest in Becoming a Teacher.